Low-Dose Ketamine Infusion for Perioperative Pain Management in Patients Undergoing Laparoscopic Gastric Bypass: A Prospective Randomized Controlled Trial - Mitchell T. Seman; Shawn H. Malan; Matthew R. Buras; Richard J. Butterfield; Kristi L. Harold; James A. Madura; David M. Rosenfeld; Andrew W. Gorlin (Anesthesiology Research and Practice)
Introduction. Obesity is a common comorbidity seen in the perioperative setting and is associated with many diseases including cardiovascular disease and obstructive sleep apnea. Laparoscopic Roux-en-Y gastric bypass is the gold standard surgical treatment for patients whose weight is refractory to diet and exercise. Caring for these patients perioperatively presents unique challenges to anesthesiologists and is associated with an increased risk of adverse respiratory events. In our study, we hypothesize that a low-dose perioperative ketamine infusion will reduce opioid consumption and improve analgesia when compared to standard therapy. Methods. This is a single-center, prospective randomized controlled study enrolling 35 patients in total. Patients were randomized equally into the ketamine and control group. Preop, intraop, and postop management regimens were standardized. The ketamine group received a 0.3 mg/kg ideal body weight ketamine bolus after induction followed by a 0.2 mg/kg/hr ketamine infusion continued into the postop setting for up to 24 hours. Data collected included total perioperative opioids used converted to oral morphine equivalents (ME), pain scores, side effects, hospital length of stay, and patient satisfaction captured via postoperative questionnaires. Results. The use of perioperative opioid consumption was significantly lower in the ketamine group when compared with the control group (179.9 ME versus 248.7 ME, P=0.03). There was no statistically significant difference in pain scores or hospital length of stay postoperatively between the two groups. There were also no reported adverse respiratory events, prolonged sedation, agitation, or other side effects reported in either group. The patient satisfaction questionnaires showed a significant difference with the ketamine group reporting lower maximum pain scores, a decrease in how pain limited activities of daily living once discharged, and increased hospital pain management satisfaction scores. Conclusions. Perioperative low-dose ketamine infusions significantly reduced opioid consumption in morbidly obese patients undergoing laparoscopic gastric bypass surgery.